Experimental Research on Failure Behavior of Soil around Pile under Compression - Yongmei Qian; Guanghan Xu; Ruozhu Wang (Institute of Advanced Engineering and Science, 2013)
Through small scale model laboratory experiments, the article proves that the effect of pile and soil work together of Push-extend Multi-under-reamed Pile under compression, and identifies failure modes and failure principle of soil around the pile, and for further determining ultimate bearing capacity of soil under compressive state about the Push-extend Multi-under-reamed Pile, it provides a reliable foundation. At the same time, this article provides a new method for laboratory test, which calls small scale model laboratory experiments used for research about soil body failure states of pile foundation. DOI: http://dx.doi.org/10.11591/telkomnika.v11i4.2377